Drug release behaviors of flexible SiO2‐polyvinyl pyrrolidone electrospun membranes responsive to multiple stimuli. Issue 40 (1st August 2022) - Zhu, Wenqian; Zhao, Yanping; Tang, Hanxia; Lv, Fengzhu; Zhang, Yihe; Guo, Sufang
Abstract: Flexible SiO2 ‐polyvinyl pyrrolidone hybrid electrospun membranes were prepared using the partially hydrolyzed tetraethyl orthosilicate as cross‐linking component based on electrostatic spinning. Then ibuprofen (IBU) was absorbed on the fiber membrane and blocked by grafting azobenzene groups. The target membranes' excellent flexibility, good water resistance, and acceptable mechanical properties were shown. When the content of SiO2 was 17%, the membranes could withstand at least 50 g tensile strength. Meanwhile and the water contact angle of the membranes was close to that of the skin, which was 68.44°. Also controlled in vitro release performance of IBU under UV irradiation at 37°C and pH of 6.5 was observed. The release behavior was well fitted by Ritger–Peppas kinetic model, suggesting the diffusion release mechanism of the drug. In addition, the membranes possessed the ability to release drugs into hydrogels by self‐driving. Thus, the easily prepared membranes possessed the potential to release drugs in different environments. Abstract :